2013
DOI: 10.3168/jds.2012-6221
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of using automatic milking system data from commercial herds for genetic analysis of milkability

Abstract: The objective of this study was to investigate how useful data from automatic milking systems used in commercial herds are for genetic analysis of milkability traits. Data were available from 4,968 Swedish Holstein and Swedish Red cows over a span of 5 yr (2004-2009) from 19 herds. The analyzed milkability traits were average flow rate, box time, milking interval, and number of milkings per day. Variance components were estimated for genetic, permanent environmental, and residual effects in first and later (se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
33
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 12 publications
12
33
4
Order By: Relevance
“…The present study found more MCD in summer and winter months and in the group of older cows (multiparous). In investigating mean MCD, Carlström et al (2013) and Castro et al (2012) obtained results similar to those of the present study, whereas Gygax et al (2007) obtained a slightly lower result, at 2.5 (range: 0.8 to 3.9 per cow). A higher MCD value in relation to the one obtained in this study was reported by Deming et al (2013; 2.8 ± 0.4 times a day), and Madsen et al (2010) reported on average as many as three milkings per day.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The present study found more MCD in summer and winter months and in the group of older cows (multiparous). In investigating mean MCD, Carlström et al (2013) and Castro et al (2012) obtained results similar to those of the present study, whereas Gygax et al (2007) obtained a slightly lower result, at 2.5 (range: 0.8 to 3.9 per cow). A higher MCD value in relation to the one obtained in this study was reported by Deming et al (2013; 2.8 ± 0.4 times a day), and Madsen et al (2010) reported on average as many as three milkings per day.…”
Section: Discussionsupporting
confidence: 86%
“…Lower mean MCD values, i.e. from 2.1 to 2.5, were observed by WagnerStorch and Palmer (2013), Hogeveen et al (2001), Mačuhová et al (2003), Carlström et al (2013) and Bach et al (2009).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…As the interaction term between breed and annual milk yield was nonsignificant, reasons other than just higher milk production must explain the difference between HOL and NR. One possible explanation could be the generally better milkability of the HOL breed (i.e., quicker milk release and larger minute flow; Carlström et al, 2013). These characteristics may be associated with milk leaking tendency and a looser teat canal, which predispose the udder to bacterial invasion via the teat opening.…”
Section: Discussionmentioning
confidence: 99%